Hand dominance on grip strength and muscle activity among physical education pre-service teacher - Abd. Razak, Norfarahain (2015)
Hand dominance refers to the consistency of favouring to manipulate one hand over the other for the daify skiffed activity. This study was design to evaluate the grip strength and muscle activity for the right- and left-hand dominant among preservice physical education teacher.Fifteen (8 right-handed and 7 left-handed) subjects aged between 24-26 years old were involved in the study. The measurement of the hand grip strength and muscle activity had been measured using the EMG If (Hand Dynamometer) - BIOPAC Student LaM>. The results revealed that the right-hand grip dominant subjects exhibited stronger isometric strength and higher muscle activity than the left-hand grip dominant counterparts. However, no significance differences were shown on the grip strength between right-handed with left-handed subjects. On the other hand, significant differences had shown on the muscle activity on dominant hand preferences (t=2.45, p=0.03) and nolHiominant hand preferences (1=3.10, p=0.008) between right-handed and left-handed SUbjects. The differences of muscle activity amplitude indicate that the non-dominant hand grip requires more electrical impulse generated by muscle cens to after the motor control in undergoing the grip strength test.